Short Telomeres: Cause and Consequence in Liver Disease - Penrice, Daniel D.; Simonetto, Douglas A. (Seminars in Liver Disease, 2020)
Short telomere syndrome is a genetically inherited syndrome resulting in premature telomere shortening. This premature shortening of telomeres can result in hematologic, pulmonary, vascular, gastrointestinal, and hepatic manifestations of disease. Identifying patients with short telomere syndrome can be a clinical challenge due to the multitude of potential manifestations and lack of widely available diagnostic tests. In this review, we will highlight hepatic manifestations of short telomere syndrome with a focus on diagnosis, testing, and potential treatments.
Keywords: telomere; cirrhosis; portal hypertension; telomerase